Williams obstetrics - Cunningham, F. Gary; Leveno, Kenneth J.; Dashe, Jodi S.; Hoffman, Barbara L.; Spong, Catherine Y.; Casey, Brian M. (McGraw Hill, 2022)
The landmark text that has served generations of obstetrician-gynecologists fully updated with the most current perspectives of the field. Williams Obstetrics has defined the discipline for generations of obstetrician-gynecologists. Written by authors from the nationally renowned University of Texas Southwestern Medical Center and Parkland Hospital, the new edition of this authoritative, evidence-based work maintains its trademark comprehensive coverage and applicability at the bedside, while offering the most current information and insights. The culmination of a century of clinical thought, Williams Obstetrics, 26th Edition delivers expert coverage of obstetrical complications, such as preterm labor, pregnancy-related hypertension, infection, and hemorrhage. It additionally offers foundational content on reproductive anatomy, physiology, and prenatal care.